The Effects of Group-Based versus Individual-Based Tai Chi Training on Nonmotor Symptoms in Patients with Mild to Moderate Parkinson’s Disease: A Randomized Controlled Pilot Trial - Jing Hui Yang; Ya Qun Wang; Sai Qing Ye; You Gen Cheng; Yu Chen; Xiao Zhen Feng (Parkinson's Disease)
Objective. To compare the effects of group-based and individual-based Tai Chi training on nonmotor symptoms in patients with mild to moderate Parkinson’s disease. Design. Randomized controlled pilot study. Methods. 36 community-dwelling patients with Parkinson’s disease (PD) were randomly assigned to either group-based training group (n=19) or individual-based group (n=17). Both groups received same content of Tai Chi training 3 times a week for 13 weeks. Participants were also asked to perform home exercises daily. The Non-Motor Symptoms Scale was used to assess global nonmotor symptoms change. Sleep quality, depression, and cognition were evaluated by Parkinson’s Disease Sleep Scale, Hamilton Depression Scale, and Beijing version-Montreal Cognitive Assessment, respectively. Home exercise compliance was recorded. Results. There was no significant difference between two groups at baseline. After 13 weeks, there were no statistical significance between two groups. However, the within-group effect was different. Participants in group-based and individual-based groups showed a significant improvement on global nonmotor symptoms (P<0.001, P=0.004) and sleep (P<0.001, P<0.001). But only group-based training patients presented a significant improvement in cognitive impairment compared with baseline (P=0.002, P-0.116). For depression, no group gained a significant improvement(P=0.123, P=0.170). Group-based participants had a higher home-exercise compliance rate (HeCR) than individual-based participants did (P=0.019), and HeCR showed a moderate correlation with MoCA-BJ and NMSS scores changes in this study. Conclusion. Group-based Tai Chi training is considered to be a more effective and a more labor-saving method in the clinical settings, and patients tend to have a higher compliance rate in their home exercise program. This study is registered with ChiCTR-IPR-17010388.